História de vida de professores de língua portuguesa do PROEJA no IFPA - Carvalho, José Raimundo (2010)
The present study has been aimed to learn the history of the life of Portuguese teachers of Proeja at IFPA through experiences and discussions involving EJA in the teaching orality. The purpose of the study was to analyze the Portuguese teachers’ understanding concerning PROEJA itself and the Portuguese Language Program, in the sense of doing and learning in the Integrated Education, Proeja. The methodology used was qualitative research as instrument of bibliographical and documental analysis and the interview of the history of life testimonies for being the most appropriate for the creation of narratives, considering it as a gateway to the social realities, because of the reconstruction of the past. The theoretical background is based on the studies of Hadad (2008) Soares (2008) Delgado (2006), Bosi (2009), Minayo (2008), Poupart (2008), Luckesi (2008) to name some. The research revealed that the testimonies showed the knowledge variability and attitudes before the callings of the educational reflections, even though the teachers have been aware of the educational process. The research showed the variability in the understanding of Proeja and the lack of attendance of IFPA Portuguese Program when it comes to Proeja. The conclusion is that the teachers who teach in the Program are capable of passing the subject, but they need to study more about the conceptions, the principles and the objectives of Proeja.